(untitled) (Educational Knowledge, 2024)
The outcomes of academic endeavors aimed at the comprehensive development of students in capacities, values, and skills for inclusion and equal opportunities are presented. Through shared experiences, the intention is to broaden understanding of inclusive design concerning the needs of individuals with disabilities, fostering effective social interactions in lived spaces imbued with diverse meanings. The integration of this theme into the academic sphere has been facilitated through classroom experiences, research initiatives, and extension projects. Significant emphasis is placed on the transversal integration of Inclusive Design within the Architecture program, recognizing the university’s capacity to facilitate social interaction, active community participation, and the application of academic, research, and human resources to address social challenges and relevant knowledge within the academic context.